ROLE OF PHYSIOLOGY IN CRICKET - Babu, Mr.P.Madhusudhana (The journal of contemporary issues in business and government, 2009)
Despite its long history and global appeal, relatively little is known about the physiological and other requirements of cricket. It has been suggested that the physiological demands of cricket are relatively mild, except in fast bowlers during prolonged bowling spells in warm conditions. However, the physiological demands of cricket may be underestimated because of the intermittent nature of the activity and the generally inadequate understanding of the physiological demands of intermittent activity. Here, we review published studies of the physiology of cricket. We propose that no current model used to analyse the nature of exercise fatigue (i.e. the cardiovascular anaerobic model, the energy supply energy depletion model, the muscle power muscle recruitment model) can adequately explain the fatigue experienced during cricket.